2021
DOI: 10.1038/s41598-021-82927-5
|View full text |Cite
|
Sign up to set email alerts
|

DFT, Monte Carlo and molecular dynamics simulations for the prediction of corrosion inhibition efficiency of novel pyrazolylnucleosides on Cu(111) surface in acidic media

Abstract: Five novel pyrazolylnucleosides have been evaluated theoretically for their corrosion inhibition efficiency on the Cu(111) surface in acidic media. DFT calculations were carried out to exhibit the intrinsic properties such as lowest unoccupied (ELUMO) and highest occupied (EHOMO) molecular orbital energies, as well as energy gap (∆E), chemical hardness (η), chemical softness (σ), electronegativity (χ), electrophilicity (ω) and nucleophilicity (ε). The theoretical FT-IR spectra were recorded to indicate the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 104 publications
0
20
0
1
Order By: Relevance
“…When the electron affinity and ionization potential of the material were computed, a comparable capacity was obtained. Additionally, the proclivity of the forms of Pantoprazole for adsorption on metal surfaces were enhanced by an appropriate softness value and a relatively low hardness ratio [9,11,46,47].…”
Section: Dft MC and Md Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the electron affinity and ionization potential of the material were computed, a comparable capacity was obtained. Additionally, the proclivity of the forms of Pantoprazole for adsorption on metal surfaces were enhanced by an appropriate softness value and a relatively low hardness ratio [9,11,46,47].…”
Section: Dft MC and Md Resultsmentioning
confidence: 99%
“…When it comes to Pantoprazole, the HOMO and LUMO were significant due to their ability to interact with the Fe (1 1 0) surface via electron donation and acceptation, respectively[2,7,21,[24][25][26][27][29][30][31]36,[43][44][45].When the electron affinity and ionization potential of the material were computed, a comparable capacity was obtained. Additionally, the proclivity of the forms of Pantoprazole for adsorption on metal surfaces were enhanced by an appropriate softness value and a relatively low hardness ratio[9,11,46,47].…”
mentioning
confidence: 99%
“…Molecular dynamics simulation has been reported to be a recognized method introduced to corrosion studies 34 . This approach gives insight into the inhibitors' interactions, orientation, and binding energies involving the inhibitors and metal surface 26,35 . In this work MD simulations were adopted to complement the experimental results obtained and to study the mechanism of interactions between the inhibitors and the Fe (1 1 0) surface as well as in the presence of 200 water, H3O + and Cl -.…”
Section: Molecular Dynamics (Md) Simulationmentioning
confidence: 99%
“…and the vacant orbitals of the positively charged Fe (1 1 0) surface 35 . The MD simulation revealed that notwithstanding the presence of the corrosive elements such as H3O + , Cland the water molecules, a strong interaction exist between the surface of the metal and the heteroatoms (O, N, and the phenyl ring) of L1 and L2.…”
Section: Molecular Dynamics (Md) Simulationmentioning
confidence: 99%
“…Incluso existe el método de Car-Parrinello, que se puede considerar como un híbrido entre MD y DFT (Car y Parrinello, 1985). Asimismo, existen algunos artículos (Qin et al, 2010;Oukhrib et al, 2021) en los que se aplican ambos niveles de teoría a un mismo sistema para estudiar parámetros distintos que no se pueden (o sería extraordinariamente complejo) estudiar con una sola teoría, es decir, a esa escala son complementarias.…”
unclassified